Data on water, sanitation, and hygiene in six select metro cities of India - Shashi Kala Saroj; Srinivas Goli; Md Juel Rana; Bikramaditya K. Choudhary (Data in Brief, 2020)
The purpose of this data article is to describe the data and provide the methodological notes on the construction of availability, accessibility, and overall Water, Sanitation and Hygiene (WASH) performance index using a set of thirteen indicators for six metro cities in India. It also presents the details on survey design and the nature of data collected on WASH indicators in India Human Development Survey for 2004–05 (IHDS-I) and 2011–12 (IHDS-II). The principal component analysis (PCA) procedure was used in the construction of the WASH indices. The IHDS is the only survey that provides comprehensive data on WASH indicators for six metro cities in India (Delhi, Mumbai, Kolkata, Chennai, Hyderabad, & Bangalore). The IHDS has been jointly conducted by researchers from the National Council of Applied Economic Research (NCAER), New Delhi and the University of Maryland, the United States of America (USA). The database is hosted in the public repository at the Inter-University Consortium for Political and Social Research (ICPSR) and the reference number for IHDS-I and IHDS-II are ICPSR 22626 and ICPSR 36151 respectively. The data are publicly available through ICPSR. Interpretation of the present data can be found in the research article titled “Availability, accessibility, and inequalities of water, sanitation, and hygiene (WASH) services in Indian metro cities” (Saroj et al., 2019) [9]. Keywords: WASH, Metro cities, India, India human development survey